2004
DOI: 10.1182/blood-2003-08-2968
|View full text |Cite
|
Sign up to set email alerts
|

Membrane type 1–matrix metalloproteinase (MT1-MMP) cooperates with sphingosine 1–phosphate to induce endothelial cell migration and morphogenic differentiation

Abstract: Membrane type 1-matrix metalloproteinase (MT1-MMP) has been suggested to play an important role in angiogenesis, but the mechanisms involved remain incompletely understood. Using an in vitro model of angiogenesis in which cell migration of bovine aortic endothelial cells (BAECs) and their morphogenic differentiation into capillary-like structures on Matrigel are induced by overexpression of MT1-MMP, we show that the plateletderived bioactive lipid sphingosine 1-phosphate (S1P) is the predominant serum factor e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
109
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 92 publications
(117 citation statements)
references
References 60 publications
8
109
0
Order By: Relevance
“…These morphologic changes were also inhibited by BB94 (30% of the GFP-positive cells showed a migratory phenotype; Fig. 2), a broad-spectrum metalloprotease inhibitor, which is in keeping with our previous study showing that MT1-MMPdependent BAEC migration involves the catalytic activity of the enzyme (13). In addition, overexpression of a catalytically inactive MT1-MMP mutant (E240A) and treatment with MT1-MMP physiologic tissue inhibitors of metalloproteinase (TIMP-2 and TIMP-3) inhibited the ability of MT1-MMP to induce BAEC migratory phenotype (data not shown).…”
Section: Mt1-mmp -Dependent Morphogenic Differentiation and Endothelisupporting
confidence: 91%
See 4 more Smart Citations
“…These morphologic changes were also inhibited by BB94 (30% of the GFP-positive cells showed a migratory phenotype; Fig. 2), a broad-spectrum metalloprotease inhibitor, which is in keeping with our previous study showing that MT1-MMPdependent BAEC migration involves the catalytic activity of the enzyme (13). In addition, overexpression of a catalytically inactive MT1-MMP mutant (E240A) and treatment with MT1-MMP physiologic tissue inhibitors of metalloproteinase (TIMP-2 and TIMP-3) inhibited the ability of MT1-MMP to induce BAEC migratory phenotype (data not shown).…”
Section: Mt1-mmp -Dependent Morphogenic Differentiation and Endothelisupporting
confidence: 91%
“…1B). Although a close cooperation between the S1P-and the vascular endothelial growth factor -mediated signaling cascades has been identified in some cell systems, we have previously shown that the S1P-stimulated MT1-MMP -dependent endothelial cell migration and morphogenic differentiation do not involve vascular endothelial growth factor receptor activity (13). To determine whether the stimulatory effect of S1P involves the transactivation of other receptor tyrosine kinases, such as PDGFR (24), and EGFR (24, 25), we tested AG1478 and AG1296, two selective inhibitors of EGFR and PDGFR tyrosine kinase activities, respectively.…”
Section: Mt1-mmp -Dependent Morphogenic Differentiation and Endothelimentioning
confidence: 81%
See 3 more Smart Citations